Translating Wordplay in A Comedy Movie: Strategies and Their Effectiveness Viewed from a Multimodal Perspective (e-Journal of Linguistics, 2023)
This descriptive qualitative research on audiovisual translation aims todescribe and analyze two elements, namely, the wordplay translationstrategies applied by the translator in Scary Movie 3 and theeffectiveness of the strategies from a multimodality perspective. Threeinstruments were used in collecting data; transcription sheet, selectionsheet and category matrix. The result revealed that four strategies wereimplemented in translating wordplay in this movie: wordplaytranslation into non-wordplay, zero translation, wordplay translation byborrowing the wordplay of the source language, and wordplaytranslation to wordplay with a related rhetorical device. Furthermore, itwas also found that the effectiveness of the strategies was supported bythe existence of images (nonverbal visual channel (NVC)), backgroundsounds (nonverbal auditory channel (NAC)), dialogue (verbal auditorychannel (VAC)), and the subtitles (verbal-visual channel (VVC)). Theholistic analysis of all polysemiotic channels in the scenes show that thecharacteristics of audiovisual translation does not align themonosemiotic translation. The existence of the semiotic channels allowthe text compression in the subtitle without reducing the naration flow.
Keywords: Audiovisual translation; translation strategy; effectiveness; multimodality